METRO files : Peradaban yang ditinggalkan (Batujaya) [rekaman video] / editor, Ronald Tasliman, Fernanda, Andi Charis - Ronald Tasliman; Fernanda; Andi Charis (Metro TV, 2009)
DVD : digtital, stereo ; 4 3/4 in